Clinico-Ultrasonographic Profile of Ectopic Pregnancy in Western Nepal - Gurung, Sangeeta Devi; Sharma, Prakash (Nepalese Journal of Radiology, 2018)
Introduction: Ectopic pregnancy (EP) is one of the major complications in first trimester pregnancy, resulting in increased maternal morbidity and mortality. It accounts for 1.3-2.4% of all pregnancies. Previously, though laparoscopy was considered as the gold standard for diagnosis of ectopic pregnancy, due to availability of high resolution ultrasound, it has become the first line investigation for the diagnosis of ectopic pregnancy. Methods: It is a prospective study conducted in Manipal Teaching Hospital, Pokhara, from January 2015 till December 2017. All the cases diagnosed with ectopic pregnancy were included in the study. Ultrasonological and intraoperative findings were recorded. Data was analyzed using SPSS (VERSION 16). Results: Twenty six patients were diagnosed with ectopic pregnancies. The incidence was 0.35%. It was most common among the reproductive age group between 20-40 years with mean age of 30.50 years. Pelvic inflammatory disease (n=10, 38.5%) was considered as risk factor. Radiological finding of Type III ectopic pregnancy (n=21, 80.8%) was the most common type. Conclusion: Ectopic pregnancy is common among reproductive age group with previous history of pelvic inflammatory disease. Type III is the most common type.